Pengaruh Experiential Marketing, Service Quality dan Reference Group terhadap Kepuasan Nasabah Dengan Loyalitas sebagai Variabel Moderasi pada Bank Sumut Syariah KCP Multatuli - Effendy, M. Ridho; Nawawi, Zuhrinal M.; Aslami, Nuri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to examine the effect of experiential marketing, service quality and reference groups on customer satisfaction, either partially or simultaneously. And to test whether loyalty is able to moderate the experiential marketing, service quality and reference group variables on customer satisfaction at the North Sumatra Islamic bank Multatuli KCP. This study uses quantitative research methods by collecting data using a Likert scale. The subjects of this study were customers from Bank Sumut Syariah Kcp Multatuli, totaling 100 samples, data analysis techniques through the IBM SPSS statistics 15 program. The results of the study show that first, the experiential marketing variable has a significant effect on customer satisfaction. variable significance value (X1) experiential marketing of 0.000 (<0.05). Second, the service quality variable has a significant effect on customer satisfaction variables. the variable significance value (X2) of service quality is 0.019 (<0.05). The three reference group variables have no significant effect on customer satisfaction variables. variable significance value (X3) reference group of 0.956 (> 0.05). The four customer loyalty variables were unable to moderate the influence of experiential marketing variables on customer satisfaction. The significance value of the interaction variable between experiential marketing and loyalty was 0.946 (> 0.05). The five customer loyalty variables were unable to moderate the influence of service quality variables on customer satisfaction. The significance value of the interaction variable between service quality and loyalty was 0.276 (> 0.05). The six customer loyalty variables were unable to moderate the influence of the reference group variable on customer satisfaction. The significance value of the interactio n variable between the reference group and loyalty was 0.941 (> 0.05). Seventh simultaneously experiential marketing (X1), service quality (X2), reference group (X3) and Loyalty (Z) have a significant effect on customer satisfaction as variable Y, and Sig value < 0.05 then 0.000 < 0.05. Keywords : Experiential Marketing, Service Quality, Reference group, Customer satisfaction and Loyalty.